Introduksi Teknologi Pengering Tenaga Surya Untuk Meningkatkan Produktivitas Dan Pendapatan Usaha Kerupuk Ubi Di Kecamatan Kamang Magek Kabupaten Agam - Adli Havendri; Dendi Adi Saputra; Eka Satria; Syafi’i Syafi’i (Department of Mechanical Engineering, Universitas Andalas, 2018)
The micro, small and medium scale of industrial enterprises for cassava crackers is growing rapidly in Kamang Magek District of Agam Regency. Cassava crackers are the typical crackers which only find in the Agam Regency. The taste is crunchy and can be stored for a long time, making this cracker a special food souvenir. In the process of making, cassava is boiled and pounded so that it becomes pasta. Pasta will be formed and dried in the sun. The crackers that have been formed should be dried in a maximum of 1 day. Today, the makers of cassava crackers are still dependent on sunlight, so they often cannot meet market demand during the rainy season. Therefore, through the IbM (Ipteks bagi Masyarakat) program for the community funded by DIKTI, solar drying technology is introduced by using a type of solar tunnel. The result shows the drying time is 2 times faster than traditional drying process. Hopefully, this technology can help the community of the cassava crackers maker to increase their productivity.